Correction to: A compact finite difference method for reaction–diffusion problems using compact integration factor methods in high spatial dimensions - Rongpei Zhang; Zhen Wang; Jia Liu; Luoman Liu (Advances in Difference Equations, 2018)
In the publication of this article [1], there is an error in one of the authors’ name. This has now been included in this correction.